A fenomenologia da imaginação em Jean-Paul Sartre, caminho para uma interpretação estética da liberdade - Rozangela Gontijo (2005)
In the treatise L'être et le Neant, Sartre refers clearly to an absolutly necessary freedom: The man is condemned to be free. The analysis of this human reality is accomplished in the imaginary where the ontologic statute of the image is explained. In the imaginary Sartre develops the unrealized function of the ilusory conscience, that shows his object as absent, against the perceptive conscience that puts this object as present and real. In conclusion Sartre says that the arts wold be the privileged place to meeting, between the conscience and the object. The relation between then is a shock, a meeting and this conception exemplify the total and absolute freedom.